Comparison of Physical Properties, Energetic, Vibration Frequencies and Normal Coordinates, for Construction Units of Fullerene C60 Using Quantum Mechanical Calculations - Kubba , Rehab Majed; Samawi, Khalida Aubead (Iraqi Journal of Science, 2022)
PM3 semiempirical method and Density Functional Theory (DFT) calculations of the type (B3LYP) and a Gaussian basis set (6-311G) were carried out for fullerene C60 molecule with its construction units (5radialene, 1,2,3-trimethylene indan, and corannulene), to evaluate the geometrical structure (bond lengths, symmetry, and energetic such as heat of formation ΔH0f, total energy Etot., dipole moment μ, EHOMO (highest occupied molecular orbital energy), ELUMO (lowest unoccupied molecular orbital energy), energy gap ΔEHOMO-LUMO), the distribution of electron density and vibration frequencies, all at their equilibrium geometries. Assignment of the vibrations modes was done according to the movement of the atoms as a result of DFT calculation using Gaussian program view. Comparison was done for the distribution of electron density with the expense of vibration frequencies and for the relationship of all the physical and electronic properties of fullerene C60 with its construction units.